2019
DOI: 10.1016/j.ecocom.2019.100773
|View full text |Cite
|
Sign up to set email alerts
|

Testing the River Continuum Concept with geostatistical stream-network models

Abstract: The River Continuum Concept (RCC) provided one of the first unifying frameworks in fluvial ecosystem theory. While the RCC predictions held in many empirical tests, other research highlighted how the model overlooked sources of heterogeneity at different scales e.g. the effects of tributaries. Disentangling these effects requires an assessment of variation in key ecosystem variables over the longitudinal and lateral dimension of river networks. However, so far, no empirical tests have employed a spatially expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 62 publications
4
28
1
Order By: Relevance
“…For example, the reliability of Dist to describe taxonomic composition of macrobenthic communities was also demonstrated by Pollice et al [18] in the river systems of Northern Italy (including river Adige basin). The decrease of predator taxa along the longitudinal gradient of the river Adige network was detected also by Larsen et al [11], who also found significant patterns for other functional groups that were not confirmed in this study.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…For example, the reliability of Dist to describe taxonomic composition of macrobenthic communities was also demonstrated by Pollice et al [18] in the river systems of Northern Italy (including river Adige basin). The decrease of predator taxa along the longitudinal gradient of the river Adige network was detected also by Larsen et al [11], who also found significant patterns for other functional groups that were not confirmed in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…Particularly, functional and structural indices were significantly correlated, and taxa richness was found to be the best predictor for pesticide concentrations. Larsen et al [11] studied the functional feeding habits of macrobenthic assemblages using a geostatistical method and observed that, even following a heterogeneous pattern along the longitudinal gradient, the distribution of feeding functional groups was generally consistent with the RCC. Similar outcomes were observed by Pollice et al [18] for structural composition of macrobenthic community of Adige and other alpine streams and rivers using asymmetric eigenvector maps that are used to detect the influence of directional spatial processes on the taxa distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To consider the position of the sampling sites in the river network and their spatial connectivity, beyond the mainstem view that the RCC employs, the authors used spatially explicit models using three different measures of distance: overland, flow-connected, and flow-unconnected. They found that downstream changes in FFGs were generally consistent with the predictions of the RCC, but this longitudinal variation was mostly patchy-discontinued rather than a gradient (Larsen et al 2019). Moreover, the spatial autocorrelation of spatially explicit modelling generally improved the performance of the statistical analysis.…”
Section: Assessing the Position In The River Network And Its Effects mentioning
confidence: 84%
“…Point 3: (25°27'43.00" S / 50°39'20.86" W) stretch with 4 m wide, on average, characterized by sandy bottom and predominantly with slab and partial presence of riparian forest. Based on the theory that rivers follow the principle of a continuum system (Larsen et al, 2019), collection points selection followed the choice criterion according to landscape composition change.…”
Section: Characterization and Location Of Study Areasmentioning
confidence: 99%